Impact analysis of tunnel crossing pile foundation at different angles - Zhongxi Tian; Zhiyu Zhang; Guangzhan Zhang; Xiangjun Shan; Wanrong Liu (Scientific Reports)
Abstract Shield method construction is a common method of urban subway tunnel excavation, shield tunneling through existing building pile foundation will produce disturbance to the surrounding strata, causing bending of the pile foundation, decreasing the bearing capacity of the pile foundation, underpinned piles is one of the commonly used problem-solving approaches. This paper takes the actual engineering project as the background, uses the finite element analysis software midas GTS NX to creating 3D computational models, and analyzes the effect of tunnel crossing on the surface settlement and pile foundation deformation when the shield tunnel and the axes of the underpinned beams are at different angles. The results show that: the smaller the angle is, the larger the surface settlement is, the maximum value is 2.5 mm, and when the angle is 90 degrees (vertical crossing), the settlement is the smallest, the minimum value is 2.0 mm; the effect of tunnel crossing on the vertical bending of the underpinned piles is relatively little, the effect on the horizontal displacement increases greatly with the decrease of the angle; the axial force and bending moment of the underpinned piles appear to be the maximum values at the location where the shield tunnel crosses. The above conclusions have important engineering significance for determining the optimal angle of shield tunneling through the pile foundation and realizing the minimum impact on the surrounding soil and pile foundation during the crossing.